SIMULTANEOUS PATHOGEN DETECTION OF SHRIMP VIRUSES ON CULTURED TIGER SHRIMPS (Penaeus monodon) IN INDONESIA - Koesharyani, Isti; Sudaryatma, Putu Eka; Gardenia, Lila; Aryati, Yani; Mahardika, Ketut; Mufidah, Tatik (Indonesian Aquaculture Journal, 2023)
The multiple-pathogen infection causes severe economic impact to shrimp industry in Indonesia and worldwide due to mass mortality and multiple abnormalities of the survived infected shrimps. However, multiple-pathogen detection tools in shrimp diseases have not yet widely used. The purpose in this study was to develop and applied simultaneous detection system using multiplex polymerase chain reaction (PCR) assay from natural infections caused by white spot syndrome virus (WSSV), infectious hypodermal and haematopoietic necrosis virus (IHHNV) and monodon baculovirus (MBV) in Black tiger shrimp culture. To analyze multiple-pathogen infections in the shrimp, the study designed and used three pairs of specific primers targeting DNA virus from the shrimp diseases. All amplifications used a specific master mix for multiplex PCR assay and standardized extracted nucleic acid from the samples. This mPCR assay successfully amplified the DNA of three viruses in a single tube-run by multiplex PCR for each virus. Based on the results, the study confirms that multiple-pathogen infection contributes the highest mass mortality rather than from single infection by either WSSV, IHHNV or MBV. This study also confirms that the mPCR assay is a faster, cheaper, and efficient method to detect and subsequently prevent the spreading of multi-pathogen shrimp diseases.